1993
DOI: 10.1128/iai.61.3.1062-1068.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a conserved helper-T-cell epitope from group A Streptococcal M proteins

Abstract: We have previously defined major histocompatibility complex (MHC) class II-restricted T-cell epitopes from the carboxy-terminal region of group A streptococcal type 5 M protein. In this report, T-cell responses to one of these epitopes have been characterized in detail. T-cell clones from recombinant M5-immunized mice and popliteal lymph node cells from peptide-immunized mice were used to show that sM5[300-3191 is recognized in the context of I-A alleles of four of nine independent MHC class II haplotypes: I-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Secondly, streptococcal infection may be associated with superantigen production favouring expansion of certain TCR families associated with autoimmune responses [68]. Some, [69,70], but not all studies addressing anti-M directed T-cell responses [71,72] have suggested that the M protein itself may act as a superantigen preferentially expanding TCR Vb2, 4 and 8 subsets. The present findings show that the M6 or streptodornase B-directed T-cell responses are antigen specific based on T-cell reactivity against synthetic peptides.…”
Section: Cd8+mentioning
confidence: 99%
“…Secondly, streptococcal infection may be associated with superantigen production favouring expansion of certain TCR families associated with autoimmune responses [68]. Some, [69,70], but not all studies addressing anti-M directed T-cell responses [71,72] have suggested that the M protein itself may act as a superantigen preferentially expanding TCR Vb2, 4 and 8 subsets. The present findings show that the M6 or streptodornase B-directed T-cell responses are antigen specific based on T-cell reactivity against synthetic peptides.…”
Section: Cd8+mentioning
confidence: 99%
“…The following synthetic peptides bearing CD4 T cell epitopes were used in this study: (1) 15 EALDKYELENHDLKTK-NEG 33 containing epitope M5 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (underlined); (2) 300 DAS-REAKKQVEKALEEANSK 319 covering epitope M5 308-319 (underlined) mapped previously [43,44]; (3) p381-394, 381 LIQEMLKTMESINQ 394 containing epitope SipC 381-394 /A d of the SipC protein of Salmonella typhimurium [45]. All peptides were synthesized by the Molecular Biology Unit, University of Newcastle upon Tyne.…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…It was demonstrated that T cell clones against the carboxyterminal epitope 300-319, which has been shown to provide helper function for T-dependent IgG responses [12] , recognized peptides processed from M5, M6 and M12, but not M49, streptococci. Our results indicate that T cells against the conserved region of M5 can cross-react with other serotypes of streptococci.…”
Section: Discussionmentioning
confidence: 99%